2010
DOI: 10.3349/ymj.2010.51.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Factor VIII Gene into Skeletal Muscle Cells Using Lentiviral Vector

Abstract: PurposeThis study was designed to investigate whether transduction of lentiviral vectors (LV) carrying human coagulation factor VIII (hFVIII) cDNA into skeletal muscle could increase circulating hFVIII concentrations.Materials and MethodsA LV containing bacterial LacZ gene as a control or human FVIII gene was intramuscularly administered into the thigh muscle of 5 weeks old Sparague-Dawley rats. The plasma human FVIII concentration and neutralizing anti-FVIII antibodies were measured for up to 12 weeks in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…evaluated for the treatment of other diseases, such as erythropoietin deficiency, a-1 antitrypsin deficiency, hemophilia A and Duchenne muscular dystrophy. [73][74][75][76] Skin and muscle tissues are readily accessible and are highly vascularized, making them suitable for systemic delivery of therapeutic proteins via circulation. Indeed, serum levels of therapeutic proteins reached 1000 mg ml À 1 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…evaluated for the treatment of other diseases, such as erythropoietin deficiency, a-1 antitrypsin deficiency, hemophilia A and Duchenne muscular dystrophy. [73][74][75][76] Skin and muscle tissues are readily accessible and are highly vascularized, making them suitable for systemic delivery of therapeutic proteins via circulation. Indeed, serum levels of therapeutic proteins reached 1000 mg ml À 1 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, haemophilia is now recognized as a condition amenable to gene therapy [61][62][63][64]. Strategies available include use of lentiviral (LVV) [65] and adeno-associated (AAV) [66] vectors in adult stem cells and autologous fibroblasts, in platelets and in hematopoietic stem cells; transfer by means of non-viral vectors; and repair of mutations with chimeric oligonucleotides. The studies published so far have, in the most part, not reported any severe adverse effect resulting from the application of such strategies in the clinical trials performed.…”
Section: Advanced Therapies and Induced Pluripotent Stem Cells In Thementioning
confidence: 99%
“…Since those results were published, use of lentiviral vectors has not ceased to grow. Thus, Jeon et al [36] transduced this type of viral vector into skeletal muscle to increase factor VIII expression. Factor VIII plasma levels at one week post-injection were 5.19 ng/mL vs 0.21 ng/mL in control rats, with those levels staying constant over 4 weeks with a single dose of the vector.…”
Section: Advanced Therapies For the Treatment Of Hemophiliamentioning
confidence: 99%